Roles of clonal parental effects in regulating interspecific competition between two floating plants - Yu, Wen-Han; Zhang, Li-Min; Luo, Fang-Li; Yu, Fei-Hai; Li, Mai-He (Frontiers in Plant Science, 2022)
Parental effects can influence offspring fitness, which may further impact interspecific competition. However, few studies have tested the role of clonal parental effects in regulating interspecific interactions and examined the underlying mechanisms. We conducted two consecutive experiments with two clonal plants (Pistia stratiotes and Eichhornia crassipes). In the first experiment, the mother ramet of P. stratiotes and E. crassipes were grown in two nutrient levels and treated with a DNA demethylation reagent (5-azacytidine) or not. In the second experiment, the offspring ramets from each of the four treatments in the first experiment were grown alone (no competition) or with a heterospecific neighbor (with interspecific competition). We found no parental nutrient effect on the competitive ability of E. crassipes, but a significant parental nutrient effect of both E. crassipes and P. stratiotes on the competitive ability of P. stratiotes. Furthermore, the parental nutrient effect of P. stratiotes on the competitive ability of P. stratiotes varied depending on the DNA methylation status of both P. stratiotes and E. crassipes. These clonal parental effects were related to resource provisioning and/or DNA methylation. We conclude that clonal parental nutrient effects can regulate interspecific competition between P. stratiotes and E. crassipes by altering the competitive ability of P. stratiotes. Both resource provisioning and epigenetic mechanisms can be involved in these clonal parental effects. By regulating interspecific competition, clonal parental effects may further influence species coexistence, community structure and ecosystem functioning.